White adipose tissue: storage and effector site for environmental pollutants - Müllerová, D; Kopecký, J (Physiological research, 2007)
White adipose tissue (WAT) represents a reservoir of lipophilic environmental pollutants, especially of those which are resistant to biological and chemical degradation - so-called persistent organic pollutants (POPs). Large amounts of different congeners and isomers of these compounds exhibit a variety of adverse biological effects. Interactions among different classes of compounds, frequently with opposing effects, complicate hazard evaluation and risk assessment. WAT is the key organ for energy homeostasis and it also releases metabolites into the circulation and adipokines with systemic effects on insulin sensitivity and fuel partitioning in muscles and other tissues. Its beneficial role is lost in obesity when excessive accumulation of WAT contributes to severe diseases, such as diabetes. POPs may crossroad or modulate the effect of endogenous ligands of nuclear transcription factors, participating in differentiation, metabolism and the secretory function of adipocytes. These mechanisms include, most importantly: i) endocrine disrupting potency of POPs mixtures on androgen, estrogen or thyroid hormone metabolism/functions in WAT, ii) interference of dioxin-like chemicals with retinoic acid homeostasis, where impact on retinoid receptors is expected, and iii) interaction with transcriptional activity of peroxisome proliferator-activated receptors is likely. Thus, the accumulation and action of POPs in WAT represents a unitary mechanism explaining, at least in part, the effects of POPs in the whole organism. By modulating WAT differentiation, metabolism and function, the POPs could affect not only the physiological role of WAT, but they may also influence the development of obesity-associated diseases.
Keywords: energetický metabolismus; Endocrine Disruptors; hormony; adipogeneze; polychlorované bifenyly; Transcription, Genetic; látky znečišťující životní prostředí; Polychlorinated Biphenyls; Polychlorinated Dibenzodioxins; bílá tuková tkáň; Adipose Tissue, White; genetická transkripce; endokrinní disruptory; Hormones; Animals; lidé; Energy Metabolism; Transcription Factors; Adipogenesis; transkripční faktory; Humans; zvířata; polychlorované dibenzodioxiny; Environmental Pollutants